Cell-Free Translation of Paramyxovirus Messenger RNA - Kingsbury, D. W. (1973)
Polypeptides corresponding in electrophoretic mobility to virion polypeptides 1, 3, and 5 were made in a reticulocyte cell-free system to which 18S RNA from Sendai virus-infected cells was added. Immune precipitation was used to select relevant polypeptides from endogenous products. The cell-free product corresponding to virion polypeptide 3 (the nucleocapsid structure unit) was the most abundant; its tryptic peptides comigrated electrophoretically with tryptic peptides of polypeptide 3 isolated from virions. Other sedimenting classes of RNA from infected cells were tested; only the 28S fraction showed slight activity. Virion 50S RNA was inactive. These findings support the hypothesis that complementary RNA transcripts of paramyxovirion RNA are the templates for viral proteins.